Citrate-Coated Silver Nanoparticles Interactions with Effluent Organic Matter: Influence of Capping Agent and Solution Conditions - Gutierrez, Leonardo; Aubry, C.; Cornejo, M.; Croue, Jean-Philippe (American Chemical Society, 2015)
Fate and transport studies of silver nanoparticles (AgNPs) discharged from urban wastewaters containing effluent organic matter (EfOM) into natural waters represent a key knowledge gap. In this study, EfOM interfacial interactions with AgNPs, and their aggregation kinetics were investigated by atomic force microscopy (AFM) and time-resolved dynamic light scattering (TR-DLS), respectively. Two well-characterized EfOM isolates, i.e., wastewater humic (WW humic) and wastewater colloids (WW colloids, a complex mixture of polysaccharides-proteins-lipids), and a River humic isolate of different characteristics were selected. Citrate-coated AgNPs were selected as representative capped-AgNPs. Citrate-coated AgNPs showed a considerable stability in Na+ solutions. However, Ca2+ ions induced aggregation by cation bridging between carboxyl groups on citrate. Although the presence of River humic increased the stability of citrate-coated AgNPs in Na+ solutions due to electrosteric effects, they aggregated in WW humic-containing solutions, indicating the importance of humics characteristics during interactions. Ca2+ ions increased citrate-coated AgNPs aggregation rates in both humic solutions, suggesting cation bridging between carboxyl groups on their structures as a dominant interacting mechanism. Aggregation of citrate-coated AgNPs in WW colloids solutions was significantly faster than those in both humic solutions. Control experiments in urea solution indicated hydrogen bonding as the main interacting mechanism. During AFM experiments, citrate-coated AgNPs showed higher adhesion to WW humic than to River humic, evidencing a consistency between TR-DLS and AFM results. Ca2+ ions increased citrate-coated AgNPs adhesion to both humic isolates. Interestingly, strong WW colloids interactions with citrate caused AFM probe contamination (nanoparticles adsorption) even at low Na+ concentrations, indicating the impact of hydrogen bonding on adhesion. These results suggest the importance of solution conditions and capping agents on the stability of AgNPs in solution. However, the characteristics of organics would play a crucial role in the fate and transport of these nano contaminants in urban wastewaters and natural water systems.